Textile needle steel with excellent fatigue life and method for manufacturing the same
Patent Information
- Application Number
- CN202611194140.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0010]本发明针对我国纺织针等用途高碳过共析工具钢夹杂和偏析严重、脆性大韧性差、疲劳寿命短等问题,提供了一种疲劳寿命优异的纺织针用钢及其制造方法,冷轧带钢厚度0.5~2mm,珠光体球化率100%,球化直径不超过1.5μm,硬度160~220HV,表面硬度差在±5HV以内,热处理后硬度在700HV以上,抗拉强度≥1800MPa,成品纺织针的疲劳寿命≥1.2×107次
本发明通过化学成分和工艺改进,生产出一种厚度为0.5~2mm的纺织针用钢;采用Cr、Ce等元素合金化,同时控制冶炼、连铸、加热、热轧、冷却、退火、冷轧、热处理等过程的工艺参数,无需RH处理和控制连铸过热度,所得到的冷轧带钢各类非金属夹杂不超过1.0级,碳偏析度不超过1.05级,无石墨等偏析相,珠光体球化率达到100%,球化碳化物直径不超过1.5μm;钢板全板宽厚度精度±0.03mm,硬度160~220HV,表面硬度差在±5HV以内,抗拉强度950~1050MPa,屈服强度700~800MPa,断后伸长率≥18%,表面粗糙度Ra≤0.2μm。冷轧带钢经连续热处理后得到均匀细小的针状马氏体和少量残余奥氏体(5%~8%)的混合组织,针状马氏体的针长不超过15μm;热处理后成品带钢的硬度在700HV以上,表面硬度差在±5HV以内,抗拉强度≥1800MPa。采用该材料制成的纺织针疲劳寿命≥1.2×107次。
Smart Images

Figure CN122979747A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallurgical technology, and in particular to a textile needle steel with excellent fatigue life and its manufacturing method. Background Technology
[0002] Textile needles are the core loop-forming components of knitting machinery. Primarily made of steel wire or strip through precision machining, they perform the core functions of yarn hooking, loop winding, and fabric formation. Widely used in various textile equipment such as flat knitting machines, circular knitting machines, and warp knitting machines, they are crucial foundational components for achieving efficient and high-quality knitted production in the textile industry. Under high-speed, continuous, and reciprocating operating conditions, textile needles must withstand long-term cyclic fatigue stress, yarn friction and wear, and repeated bending deformation. Their service life, dimensional accuracy, and mechanical stability directly determine the quality of knitted fabrics, production efficiency, and equipment operating costs. Since steel is used as the core base material for textile needles, its material composition, structure, purity, and comprehensive mechanical properties are the core factors determining the quality of the finished product.
[0003] As the textile industry develops towards automation, high speed, and precision, the operating speed of textile machinery continues to increase, and knitting yarns are gradually extending towards diversified directions such as high-elasticity yarns, chemical fiber filaments, and specialty fibers, constantly upgrading the performance requirements for textile needles. On the one hand, under high-speed operation, key parts of textile needles, such as the hook, latch, and shank, need to have high hardness and high wear resistance to avoid dimensional wear and surface scratches caused by long-term friction with the yarn, ensuring the accuracy of coil forming. On the other hand, periodic reciprocating motion and frequent bending require materials to have excellent fatigue strength and toughness matching to prevent fatigue fracture and bending cracks during service, reduce the frequency of equipment downtime for needle replacement, and reduce production losses. At the same time, textile needles are mostly ultra-thin, irregularly shaped precision structures, and the processing process requires multiple processes such as cold rolling, stamping, bending, and heat treatment. It also requires the base material to have good cold working formability and heat treatment compatibility to avoid cracking and deformation problems during processing.
[0004] Textile needle steel is primarily composed of high-carbon steel and micro-alloyed high-carbon steel. The industry commonly uses carbon tool steels such as 72B and SK85, achieving basic control over material strength and hardness by adjusting carbon content and alloy composition. However, the high carbon content leads to severe segregation and inclusions within segregation bands. Traditional textile needle steel controls inclusions and segregation through smelting and continuous casting processes, but cannot effectively control non-metallic inclusions such as sulfides and oxides. Large, irregular inclusions can become fatigue crack initiation points, significantly reducing the fatigue life of textile needles. Furthermore, carbon segregation causes uneven carbide distribution and coarse grains, resulting in poor cold working performance, easy cracking during bending and stamping, and insufficient uniformity of hardness after heat treatment. Additionally, traditional materials struggle to balance wear resistance and toughness; while high carbon content increases hardness, it also exacerbates brittleness, making them unsuitable for the demanding conditions of high-speed textile equipment and the weaving of special fibers.
[0005] Chinese patent application No. 200510110462.X discloses a "high-purity steel strip for textile needles and its production method." The chemical composition of the steel is C: 0.9%–1.0%, Mn: 0.35%–0.50%, Si: 0.15%–0.30%, P≤0.030%, Cr: 0.15%–0.30%, and S≤0.007%. The raw material hot-rolled steel strip undergoes a single annealing-single cold rolling-second annealing-second cold rolling-third annealing process to obtain a spherical pearlitic cold-rolled high-carbon strip steel. 95% of the carbides have a particle size of 1.5–2.5 μm, with no Widmanstätten structure or banded structure, and a hardness of 255±15 Hv. However, the process involves multiple annealing and cold rolling, resulting in complex technology, low production efficiency, and high cost. Furthermore, while the extremely low sulfur content design significantly reduces hot brittleness and inclusions, the desulfurization cost during smelting is high.
[0006] Chinese patent application No. 202110827891.8 discloses "an SK85 carbon tool steel". The chemical composition of the steel is C: 0.80%~0.90%, Si≤0.35%, Mn≤0.50%, P≤0.030%, S≤0.030%, Cr≤0.30%, Ni≤0.25%, Cu≤0.25%. The metallographic structure is uniform granular / spherical pearlite, without coarse grains or network carbides, and the hardness is HV170~250. The process involves stress-relief annealing at 650℃ in a bell-type annealing furnace for 10 to 12 hours, followed by pickling, softening annealing at 730℃ in a bell-type annealing furnace for 14 hours, cold rolling, and repeated spheroidizing annealing at 680℃, 720℃, and 750℃ in a bell-type annealing furnace. This process is complex, has low production efficiency, high cost, and the surface is prone to oxidation and decarburization, which affects wear resistance and fatigue life.
[0007] Chinese patent application No. 201911340909.0 discloses a "manufacturing process for high-carbon tool steel SK85 cold-rolled wide steel strip". The chemical composition of the steel is C: 0.82%~0.88%, Si: 0.12%~0.28%, Mn: 0.25%~0.45%, P≤0.025%, S≤0.010%, Cr≤0.05%, Ni≤0.05%, Cu≤0.05%, with the remainder being Fe and impurities. The production process is: LF furnace refining - continuous casting - hot rolling - pickling - first cold rolling + first spheroidizing annealing + second cold rolling + second spheroidizing annealing + third cold rolling. The cold-rolled wide steel strip has a uniform and fine spheroidized pearlite structure without network carbide defects. The hardness is stable at 170~250HV. However, it uses multiple spheroidizing annealing and multiple cold rolling processes, which are complex, have low production efficiency, and high cost.
[0008] Chinese patent application No. 202511531303.0 discloses an "efficient manufacturing process for SK85 cold-rolled wide steel strip of high-carbon tool steel," including hot-rolling pretreatment, nano-composite lubrication, and online induction heat treatment. Through multi-pass warm rolling, it reduces deformation resistance and edge crack risk. Combined with precise shape and residual stress control, it can produce SK85 cold-rolled wide steel strip without offline annealing. However, it does not mention the spheroidization rate, strength, toughness, fatigue performance, etc., after cold rolling. High-carbon steel without spheroidization treatment has high pearlite lamellar brittleness, and typical segregation problems still exist, affecting its performance. Furthermore, this process is only suitable for thin steel plates below 2mm; it is not applicable to thicknesses above 2mm.
[0009] In summary, domestically produced high-end textile needle steel still lags behind international advanced levels in terms of purity control, fine microstructure regulation, and comprehensive mechanical property stability, making it difficult to meet the demands of high-precision textile machinery and high-speed intelligent production. Furthermore, the industry lacks refined control over key indicators such as inclusion grade, carbide spheroidization rate, and strength-toughness matching in textile needle steel, resulting in common problems with domestically produced textile needles, including short lifespan, easy breakage, and poor precision, thus hindering the high-end and high-efficiency development of the textile industry. Therefore, developing a new type of textile needle steel with high purity, uniform microstructure, and a combination of strength, toughness, and wear resistance, optimizing material composition design and preparation processes, and overcoming industry technical bottlenecks are crucial for achieving domestic substitution of textile needle base materials. Summary of the Invention
[0010] This invention addresses the problems of severe inclusions and segregation, high brittleness and poor toughness, and short fatigue life in high-carbon hypereutectoid tool steels used in textiles and other applications in my country. It provides a textile needle steel with excellent fatigue life and its manufacturing method. The cold-rolled strip steel has a thickness of 0.5–2 mm, a pearlite spheroidization rate of 100%, a spheroid diameter not exceeding 1.5 μm, a hardness of 160–220 HV, a surface hardness difference within ±5 HV, a hardness above 700 HV after heat treatment, a tensile strength ≥1800 MPa, and a fatigue life of ≥1.2 × 10⁻⁶ for the finished textile needles. 7 Second-rate.
[0011] To achieve the above objectives, the present invention employs the following technical solution: A textile needle steel with excellent fatigue life has the following chemical composition by weight percentage: 0.83%≤C≤0.99%, 0.1%≤Si≤0.4%, 0.3%≤Mn≤0.7%, Cr≤0.3%, 0.002%≤Ce≤0.010%, Al≤0.02%, P≤0.02%, S≤0.01%, H≤0.0002%, O≤0.002%, N≤0.006%, with the balance being Fe and unavoidable impurities. The finished strip steel has a mixed microstructure of uniform, fine acicular martensite and a small amount of retained austenite, wherein the acicular martensite needle length does not exceed 15μm, and the volume percentage of retained austenite is 5%–8%. After heat treatment, the strip steel has a hardness of ≥700HV, a surface hardness difference within ±5HV, and a tensile strength ≥1800MPa. The fatigue life of the finished textile needles is ≥1.2×10⁻⁶. 7 Second-rate.
[0012] A method for manufacturing textile needle steel with excellent fatigue life includes the following steps: (1) Smelting: This includes converter smelting and LF electric furnace refining. The converter produces basic slag with phosphorus ≤0.014%, sulfur ≤0.010%, and residual oxygen ≤0.05% before tapping. The LF furnace produces weakly basic slag with free oxygen ≤0.015% and residual oxygen ≤0.02% before leaving the station, and then Ce alloy is added. (2) Continuous casting: The continuous casting speed is 0.9~1.2m / min, the secondary cooling water flow rate is 0.10~0.30L / kg, the billet thickness is 200~250mm, and the surface temperature deviation of the billet is no more than 10℃. (3) Heating of the billet: The billet is hot-charged and fed into the heating furnace at a temperature ≥500℃. The heating furnace adopts a reducing atmosphere with an excess air coefficient of 0.7 to 0.9. The preheating section temperature is 550 to 700℃, and the holding time is more than 40 minutes. The first heating section temperature is 1000 to 1100℃, the second heating section temperature is 1150 to 1220℃, the soaking section temperature is 1150 to 1220℃, the residual oxygen content is 0.7% to 1%, and the total time in the furnace is 170 to 200 minutes. (4) Rolling and cooling: The roughing mill starts at 1160–1220℃, with a first pass reduction of 30–40 mm and a rolling speed of 4–7 m / s; the intermediate slab thickness is 30–40 mm; the finishing mill threading speed is 6–10 m / s, the finishing mill starts at 1080–1150℃, with a first pass reduction of 25–35 mm and a finishing mill finishing temperature of 900–980℃; the steel plate exits the finishing mill and enters laminar flow cooling, cooling at a rate of 30–60℃ / s to 550–660℃ before being coiled; after coiling, it is placed in a slow cooling pit for slow cooling for more than 72 hours within 10 minutes to obtain a fine lamellar pearlite + sorbite mixed structure, with pearlite cluster size not exceeding 20 μm and sorbite volume ratio exceeding 30%; (5) Pickling: After slow cooling, the steel coil is pickled in pickling solution at a pickling speed of 70-100 m / min. (6) Mask softening: The steel coil is annealed in a full-hydrogen bell-type annealing furnace. It is first heated to 650-680℃ at a rate of 100-150℃ / h and held for 4-6 hours, then heated to 700-750℃ and held for 10-14 hours. Then it is cooled to 650-680℃ at a rate of 30-50℃ / h and held for 4-6 hours, then slowly cooled to 500-550℃ at a rate of 15-25℃ / h, and finally cooled to below 200℃ at a rate of 100-200℃ / h before being taken out of the furnace. This yields a fine spheroidized pearlite structure with spheroidized carbides not exceeding 3μm in size. (7) Cold rolling: The cold rolling process involves 3 to 5 passes, with a first pass reduction of over 25% and a total cold rolling reduction of 50% to 60%. The width and thickness accuracy of the cold-rolled strip are controlled within ±0.03 mm. The non-metallic inclusions in the cold-rolled strip do not exceed grade 1.0, and the carbon segregation does not exceed 1.07. The pearlite spheroidization rate is 100%, and the diameter of the spheroidized carbides does not exceed 1.5 μm. The hardness is 160 to 220 HV, the surface hardness difference is within ±5 HV, the tensile strength is 950 to 1050 MPa, the yield strength is 700 to 800 MPa, the elongation after fracture is ≥18%, and the surface roughness Ra is ≤0.2 μm. (8) Heat treatment: Continuous heat treatment is adopted. First, the temperature is induction heated to 730-820℃ and held for 10-25 minutes. Then, it is cooled to 200-250℃ in a lead-bismuth mixture at a cooling rate of 40-60℃ / s and held in the furnace for more than 30 minutes.
[0013] In step (1), lime and lightly calcined dolomite are added during the converter smelting process to produce alkaline slag with an alkalinity R of 2.0 to 3.5 and a thickness of 70 to 100 mm. Silica, lime and fluorite are added during the LF electric furnace refining process to produce weakly alkaline slag with an alkalinity R of 1.0 to 2.0.
[0014] In step (4), high-pressure water descaling is used before roughing and finishing, and the descaling water pressure is not less than 20MPa; roughing is carried out by 3+1 rolling, and finishing is carried out by 7-pass continuous rolling.
[0015] In step (5), the pickling solution is HCl hydrochloric acid with a mass concentration of 15% to 30%.
[0016] In step (7), cold rolling is performed using a 20-roll reversible cold rolling mill.
[0017] In step (8), the mass ratio of lead to bismuth in the lead-bismuth mixture is 3:1 to 4:1.
[0018] Compared with the prior art, the beneficial effects of the present invention are: This invention produces a textile needle steel with a thickness of 0.5–2 mm through improvements in chemical composition and process. It employs alloying with elements such as Cr and Ce, while simultaneously controlling process parameters in smelting, continuous casting, heating, hot rolling, cooling, annealing, cold rolling, and heat treatment. This eliminates the need for RH treatment and control of continuous casting superheat. The resulting cold-rolled strip steel has no more than grade 1.0 for various non-metallic inclusions, no more than grade 1.05 for carbon segregation, no graphite or other segregated phases, a pearlite spheroidization rate of 100%, and a spheroidized carbide diameter of no more than 1.5 μm. The steel plate has a width and thickness accuracy of ±0.03 mm, a hardness of 160–220 HV, a surface hardness difference within ±5 HV, a tensile strength of 950–1050 MPa, a yield strength of 700–800 MPa, an elongation at break ≥18%, and a surface roughness Ra ≤0.2 μm. After continuous heat treatment, cold-rolled strip steel yields a mixed microstructure consisting of uniform, fine acicular martensite and a small amount of retained austenite (5%–8%), with the acicular martensite needles not exceeding 15 μm in length. The finished strip steel after heat treatment has a hardness above 700 HV, a surface hardness difference within ±5 HV, and a tensile strength ≥1800 MPa. Textile needles made from this material have a fatigue life ≥1.2 × 10⁻⁶. 7 Second-rate. Attached Figure Description
[0019] Figure 1This is a typical metallographic photograph of a textile needle steel with excellent fatigue life as described in this invention. Detailed Implementation
[0020] The present invention discloses a textile needle steel with excellent fatigue life. The chemical composition of the steel, by weight percentage, is as follows: 0.83%≤C≤0.99%, 0.1%≤Si≤0.4%, 0.3%≤Mn≤0.7%, Cr≤0.3%, 0.002%≤Ce≤0.010%, Al≤0.02%, P≤0.02%, S≤0.01%, H≤0.0002%, O≤0.002%, N≤0.006%, with the balance being Fe and unavoidable impurities.
[0021] The mechanism of action of each alloy component in the textile needle steel with excellent fatigue life described in this invention is as follows: C: 0.83%~0.99%.
[0022] Carbon (C) is a major solid solution strengthening element in steel. In this invention, C also reacts with Mn, Si, and Ce to form fine carbides, improving strength, hardness, and wear resistance. If the C content is below 0.83%, the steel will have low strength and hardness after heat treatment, and the needle tip of the textile needle will become blunt quickly. On the other hand, if the C content is above 0.99%, the toughness and plasticity of the steel will deteriorate, and the textile needle will be prone to brittle fracture. Therefore, this invention controls the C content between 0.83% and 0.99%.
[0023] Mn: 0.3%~0.7%.
[0024] Manganese (Mn) is relatively inexpensive and is an excellent deoxidizer and desulfurizer, as well as an essential element for ensuring the strength and toughness of steel. Manganese and iron can form a solid solution indefinitely, increasing hardness and strength. In this invention, Mn combines with Ce and S to form MnCeS. This avoids the formation of FeS at grain boundaries, which can cause hot cracks and affect stamping formability. Furthermore, the fine MnCeS precipitates also enhance strength and impact toughness. Too low an Mn content will not meet the requirements for high strength and hardness, while too high an Mn content will severely affect formability due to segregation and increase production costs. Therefore, considering factors such as cost and performance requirements, this invention controls the Mn content to be between 0.3% and 0.7%.
[0025] Si: 0.1%~0.4%.
[0026] Si is a common element in steel and is the main deoxidizer in this invention. As a non-carbide-forming element, Si dissolves in ferrite to improve hardenability and tempering resistance, increase heat treatment strength and hardness, and enhance wear resistance. This invention uses fine precipitates formed by Si and Ce to hinder dislocation movement, improving the elasticity and yield strength of textile needles and preventing needle deformation. Si is also a strong graphitizing element; when its content exceeds 0.4%, graphite precipitation easily occurs in high-carbon hypereutectoid steels, affecting wear resistance and fatigue performance.
[0027] Cr≤0.3%.
[0028] Chromium is a medium-strong carbide-forming element. Cr forms complex carbides with C, Mn, and Ce, inhibiting the segregation of C and Mn and improving the uniformity of the microstructure. Chromium can also increase the A3 and A1 temperatures, shift the GS line to the upper left, slow down austenite decomposition, improve hardenability, and enhance the oxidation and corrosion resistance of steel. This invention adds Cr appropriately based on the hardness requirements after heat treatment.
[0029] Harmful elements: P≤0.020%, S≤0.010%, H≤0.0002%, O≤0.0020%, Al≤0.020%, N≤0.0060%.
[0030] P, S, H, O, Al, and N are all unavoidable harmful impurities in steel. Their presence will seriously deteriorate the toughness of steel. Therefore, the content of P, S, H, O, Al, and N in steel should be controlled to be as low as possible.
[0031] Ce: 0.002%~0.01%.
[0032] Ce, as a microalloying element, forms composite precipitates with C and Cr, promoting carbide nucleation, pearlite spheroidization and refinement, and improving wear resistance and fatigue strength. This invention utilizes Ce to inhibit carbon aggregation at dendrite tips, reducing segregation and graphitization. Furthermore, this invention also utilizes Ce to combine with O, S, and Mn to form fine inclusions that float sufficiently, avoiding the formation of elongated MnS inclusions from S and Mn, thus improving toughness and fatigue performance. Statistics show that adding 0.002%–0.01% Ce can extend the fatigue life of textile needles by more than 20%.
[0033] The present invention discloses a method for manufacturing textile needle steel with excellent fatigue life. The production process includes smelting, continuous casting, billet heating, rolling and cooling, pickling, annealing and softening, cold rolling and heat treatment; specifically, it includes the following processes: (1) Smelting: This process includes converter smelting and LF electric furnace refining. The converter produces basic slag with phosphorus ≤0.014%, sulfur ≤0.010%, and residual oxygen ≤0.05% before tapping. The LF furnace produces weakly basic slag with free oxygen ≤0.015% and residual oxygen ≤0.02% before tapping. Then, Ce alloy is added, and inclusions are modified and fully floated to improve the purity of the steel (the various non-metallic inclusions in the finished steel do not exceed grade 1.0). Ce can also form fine carbides with C, reducing carbon segregation at the dendrite tips (carbon segregation degree does not exceed 1.07) and avoiding the formation of segregated phases such as graphite.
[0034] As a preferred method, lime and lightly calcined dolomite are added during the converter smelting process to create basic slag with a basicity R of 2.0–3.5. During the converter tapping process, slag-blocking operations are performed to reduce the amount of slag discharged during tapping, with a slag thickness of 70–100 mm. In the LF electric arc furnace refining process, silica, lime, and fluorite are added to create weakly basic slag with a basicity R of 1.0–2.0.
[0035] (2) Continuous casting: The continuous casting speed is 0.9~1.2m / min, the secondary cooling water flow rate is 0.10~0.30L / kg, the billet thickness is 200~250mm, the surface temperature deviation of the billet is not greater than 10℃, the billet cooling rate is uniform, and the microstructure is uniform.
[0036] (3) Heating of the billet: The billet is hot-charged and fed into the heating furnace at a temperature ≥500℃ to reduce the temperature difference on the billet surface and mitigate microsegregation. The heating furnace uses a reducing atmosphere with an excess air coefficient of 0.7–0.9; the preheating section temperature is 550–700℃, with a holding time of at least 40 minutes; the first heating section temperature is 1000–1100℃; the second heating section temperature is 1150–1220℃; the soaking section temperature is 1150–1220℃; the residual oxygen content is 0.7%–1%; and the total time in the furnace is 170–200 minutes. High temperatures promote the formation of fine Ce carbides, reduce segregation, control microstructure uniformity, and improve strength and toughness. Rapid heating avoids oxidation and decarburization of the billet.
[0037] (4) Rolling and cooling: The roughing rolling start temperature is 1160–1220℃, the first pass reduction is 30–40 mm, and the rolling speed is 4–7 m / s. The roughing rolling employs a high-temperature, slow rolling method to promote Cr carbide precipitation and refine the microstructure. The intermediate slab thickness is 30–40 mm. The finishing rolling threading speed is 6–10 m / s, the finishing rolling start temperature is 1080–1150℃, the first pass reduction is 25–35 mm, and the finishing rolling finish temperature is 900–980℃. The finishing rolling employs a high-temperature, slow rolling method, which helps to balance the latent and sensible heat of phase transformation, lowers the phase transformation temperature, refines the microstructure, and also helps to promote the precipitation of Cr and Ce carbides, thus refining the pearlite microstructure. The steel plate exits the finishing mill and enters laminar flow cooling, cooling at a rate of 30-60℃ / s to 550-660℃ before being coiled. Within 10 minutes of coiling, it is placed in a slow cooling pit for slow cooling for more than 72 hours to obtain a fine lamellar pearlite + sorbite mixed structure. The pearlite cluster size does not exceed 20μm, and the sorbite volume ratio is more than 30%, which is conducive to subsequent annealing and spheroidization.
[0038] As a preferred method, high-pressure water descaling is performed before both roughing and finishing rolling, with a descaling water pressure of not less than 20 MPa, in order to ensure the surface quality of the steel plate. Roughing is carried out using a 3+1 rolling process, and finishing rolling is carried out using a 7-pass continuous rolling process.
[0039] (5) Pickling: After slow cooling, the steel coils are pickled in pickling solution at a speed of 70-100 m / min to ensure the surface quality of the strip.
[0040] Preferably, the pickling solution uses HCl hydrochloric acid with a mass concentration of 15% to 30%.
[0041] (6) Mask softening: The steel coil is annealed in a full-hydrogen bell-type annealing furnace. First, it is heated at a rate of 100–150℃ / h to 650–680℃ and held for 4–6 hours, then heated to 700–750℃ and held for 10–14 hours (to avoid oxidation and decarburization). Next, it is cooled at a rate of 30–50℃ / h to 650–680℃ and held for 4–6 hours, then slowly cooled at a rate of 15–25℃ / h to 500–550℃. This process of repeated low-temperature annealing and slow cooling to the phase transformation temperature promotes the spheroidization and refinement of lamellar pearlite, achieving a spheroidization rate of 100%. Finally, it is cooled at a rate of 100–200℃ / h to below 200℃ before being removed from the furnace. The aim is to obtain a fine spheroidized pearlite structure, ensuring that the size of the spheroidized carbides does not exceed 3μm, while simultaneously improving production efficiency.
[0042] (7) Cold rolling: Cold rolling is performed in 3-5 passes, reducing the total number of rolling passes and improving productivity. The first pass reduction is over 25%, the total cold rolling reduction is 50%-60%, and the width and thickness accuracy of the cold-rolled strip is controlled within ±0.03mm. All non-metallic inclusions in the cold-rolled strip do not exceed grade 1.0, and the carbon segregation does not exceed 1.05; the pearlite spheroidization rate is 100%, and the diameter of the spheroidized carbides does not exceed 1.5μm; the hardness is 160-220HV, the surface hardness difference is within ±5HV, the tensile strength is 950-1050MPa, the yield strength is 700-800MPa, the elongation after fracture is ≥18%, and the surface roughness Ra ≤0.2μm.
[0043] As a preferred method, cold rolling is performed using a 20-roll reversible cold rolling mill.
[0044] (8) Heat treatment: Continuous heat treatment is employed, first induction heating to 730–820℃ and holding for 10–25 minutes to ensure sufficient austenitization. Then, it is cooled to 200–250℃ in a lead-bismuth mixture at a cooling rate of 40–60℃ / s and held in the furnace for at least 30 minutes (tempering treatment to eliminate martensitic stress).
[0045] Preferably, the mass ratio of lead to bismuth in the lead-bismuth mixture is 3:1 to 4:1.
[0046] like Figure 1 As shown, the microstructure of the finished strip steel obtained by the present invention is a mixture of uniform and fine acicular martensite and a small amount of retained austenite, wherein the length of the acicular martensite does not exceed 15μm, and the volume ratio of retained austenite is 5% to 8% (which helps to improve the toughness of the steel plate); after heat treatment, the hardness of the strip steel is above 700HV, the surface hardness difference is within ±5HV, and the tensile strength is ≥1800MPa.
[0047] The textile needle steel with excellent fatigue life described in this invention can be used to obtain textile needles through direct stamping or laser cutting. The fatigue life of the finished textile needles is ≥1.2×10⁻⁶. 7 Second-rate.
[0048] Unless otherwise specified, all percentages in this invention are percentages by mass.
[0049] To more intuitively illustrate the present invention, the embodiments of the present invention will be further described in conjunction with the examples. The following examples are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any technical solutions that can be obviously obtained by those skilled in the art within the scope of the technology disclosed in the present invention, including simple variations or equivalent substitutions, are all within the scope of protection of the present invention.
[0050]
Example
[0051] Table 1 - Chemical composition of steel (%)
[0052] Table 2 - Smelting and Continuous Casting Process Parameters
[0053] Table 3 - Billet Heating Process Parameters
[0054] Table 4 - Rolling and Cooling Process Parameters
[0055] Table 5 - Pickling and Softening Process Parameters
[0056] Table 6 - Cold Rolling and Heat Treatment Process Parameters
[0057] Table 7 - Mechanical Properties of Cold-Rolled Sheets and Heat-Treated Sheets
[0058] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A type of steel for textile needles with excellent fatigue life, characterized in that, The chemical composition of the steel, by weight percentage, is: 0.83%≤C≤0.99%, 0.1%≤Si≤0.4%, 0.3%≤Mn≤0.7%, Cr≤0.3%, 0.002%≤Ce≤0.010%, Al≤0.02%, P≤0.02%, S≤0.01%, H≤0.0002%, O≤0.002%, N≤0.006%, with the balance being Fe and unavoidable impurities. The microstructure of the finished strip steel is a mixture of uniform, fine acicular martensite and a small amount of retained austenite, wherein the length of the acicular martensite needles does not exceed 15μm, and the volume percentage of retained austenite is 5%–8%. After heat treatment, the hardness of the strip steel is above 700HV, the surface hardness difference is within ±5HV, and the tensile strength is ≥1800MPa. The fatigue life of the finished textile needles is ≥1.2×10⁻⁶. 7 Second-rate.
2. A method for manufacturing textile needle steel with excellent fatigue life as described in claim 1, characterized in that, Includes the following steps: (1) Smelting: This includes converter smelting and LF electric furnace refining. The converter produces basic slag with phosphorus ≤0.014%, sulfur ≤0.010%, and residual oxygen ≤0.05% before tapping. The LF furnace produces weakly basic slag with free oxygen ≤0.015% and residual oxygen ≤0.02% before leaving the station, and then Ce alloy is added. (2) Continuous casting: The continuous casting speed is 0.9~1.2m / min, the secondary cooling water flow rate is 0.10~0.30L / kg, the billet thickness is 200~250mm, and the surface temperature deviation of the billet is no more than 10℃. (3) Heating of the billet: The billet is hot-charged and fed into the heating furnace at a temperature ≥500℃. The heating furnace adopts a reducing atmosphere with an excess air coefficient of 0.7 to 0.
9. The preheating section temperature is 550 to 700℃, and the holding time is more than 40 minutes. The first heating section temperature is 1000 to 1100℃, the second heating section temperature is 1150 to 1220℃, the soaking section temperature is 1150 to 1220℃, the residual oxygen content is 0.7% to 1%, and the total time in the furnace is 170 to 200 minutes. (4) Rolling and cooling: The roughing mill starts at 1160–1220℃, with a first pass reduction of 30–40 mm and a rolling speed of 4–7 m / s; the intermediate slab thickness is 30–40 mm; the finishing mill threading speed is 6–10 m / s, the finishing mill starts at 1080–1150℃, with a first pass reduction of 25–35 mm and a finishing mill finishing temperature of 900–980℃; the steel plate exits the finishing mill and enters laminar flow cooling, cooling at a rate of 30–60℃ / s to 550–660℃ before being coiled; after coiling, it is placed in a slow cooling pit for slow cooling for more than 72 hours within 10 minutes to obtain a fine lamellar pearlite + sorbite mixed structure, with pearlite cluster size not exceeding 20 μm and sorbite volume ratio exceeding 30%; (5) Pickling: After slow cooling, the steel coil is pickled in pickling solution at a pickling speed of 70-100 m / min. (6) Mask softening: The steel coil is annealed in a full-hydrogen bell-type annealing furnace. It is first heated to 650-680℃ at a rate of 100-150℃ / h and held for 4-6 hours, then heated to 700-750℃ and held for 10-14 hours. Then it is cooled to 650-680℃ at a rate of 30-50℃ / h and held for 4-6 hours, then slowly cooled to 500-550℃ at a rate of 15-25℃ / h, and finally cooled to below 200℃ at a rate of 100-200℃ / h before being taken out of the furnace. This yields a fine spheroidized pearlite structure with spheroidized carbides not exceeding 3μm in size. (7) Cold rolling: The cold rolling process involves 3 to 5 passes, with a first pass reduction of over 25% and a total cold rolling reduction of 50% to 60%. The width and thickness accuracy of the cold-rolled strip are controlled within ±0.03 mm. The non-metallic inclusions in the cold-rolled strip do not exceed grade 1.0, and the carbon segregation does not exceed 1.
07. The pearlite spheroidization rate is 100%, and the diameter of the spheroidized carbides does not exceed 1.5 μm. The hardness is 160 to 220 HV, the surface hardness difference is within ±5 HV, the tensile strength is 950 to 1050 MPa, the yield strength is 700 to 800 MPa, the elongation after fracture is ≥18%, and the surface roughness Ra is ≤0.2 μm. (8) Heat treatment: Continuous heat treatment is adopted. First, the temperature is induction heated to 730-820℃ and held for 10-25 minutes. Then, it is cooled to 200-250℃ in a lead-bismuth mixture at a cooling rate of 40-60℃ / s and held in the furnace for more than 30 minutes.
3. The method for manufacturing a textile needle steel with excellent fatigue life according to claim 2, characterized in that, In step (1), lime and lightly calcined dolomite are added during the converter smelting process to produce alkaline slag with an alkalinity R of 2.0 to 3.5 and a thickness of 70 to 100 mm. Silica, lime and fluorite are added during the LF electric furnace refining process to produce weakly alkaline slag with an alkalinity R of 1.0 to 2.
0.
4. The method for manufacturing a textile needle steel with excellent fatigue life according to claim 2, characterized in that, In step (4), high-pressure water descaling is used before roughing and finishing, and the descaling water pressure is not less than 20MPa; roughing is carried out by 3+1 rolling, and finishing is carried out by 7-pass continuous rolling.
5. A method for manufacturing textile needle steel with excellent fatigue life according to claim 2, characterized in that, In step (5), the pickling solution is HCl hydrochloric acid with a mass concentration of 15% to 30%.
6. A method for manufacturing textile needle steel with excellent fatigue life according to claim 2, characterized in that, In step (7), cold rolling is performed using a 20-roll reversible cold rolling mill.
7. A method for manufacturing textile needle steel with excellent fatigue life according to claim 2, characterized in that, In step (8), the mass ratio of lead to bismuth in the lead-bismuth mixture is 3:1 to 4:1.
Citation Information
Patent Citations
A manufacturing process for cold-rolled wide strip of high-carbon tool steel SK85
CN110904319B
SK85 carbon tool steel
CN113621773A
Efficient preparation process of high-carbon tool steel SK85 cold-rolled wide steel strip
CN121373087A
High purity steel belt for textile needle and its production process
CN1772939A